Case Report: Chemoimmunotherapy in microsatellite-instability-high advanced goblet cell carcinoma of the colon - Mutlu, Arda Ulaş; Aytaç, Erman; Gülmez, Mehmet; Erdamar, Sibel; Özer, Leyla (Frontiers in Immunology, 2023)
Background: Mismatch repair (MMR) deficiency is a fundamental factor affecting the management and treatment outcomes of colorectal cancer (CRC). MMR status can be diagnosed by both immunohistochemistry (IHC) and PCR. Since tumors with MMR deficiency are prone to respond to immunotherapy, immune checkpoint inhibitors are used to treat those tumors. Case Presentation: A 69-year-old male patient presented to an outside clinic with weight loss and abdominal pain. Radiological investigations detected a mesenteric mass of 10 cm, and the eventual biopsy result was mucinous adenocarcinoma with a goblet cell pattern. Since the IHC result was unclear for dMMR mCRC, the diagnosis was confirmed with PCR. The patient received 8 cycles of FOLFORINOX + bevacizumab followed by FOLFOX + pembrolizumab. No adverse effect was reported related to immunotherapy which was resulted radiologic and metabolic regression. The patient underwent a cytoreductive surgery and HIPEC. The final pathology results revealed a pathological complete response and R0 resection. In the 6th month follow-up, no recurrence or metastasis was reported. Conclusion: Chemoimmunotherapy is a promising treatment modality which can also be used for mCRC. This is the index case who received chemoimmunotherapy for mucinous adenocarcinoma with a goblet cell pattern and had pCR.